The Effect of STEM Integrated Project Based Learning Model on Students' Collaboration Skills in Atomic Structure - Haleda, Padria; Isa, Ishak; Munandar, Haris; Bialangi, Nurhayati; Tangio, Julhim S; Thayban, Thayban; Kurniawati, Erga (Universitas Negeri Gorontalo, 2025)
The objective of this research is to investigate the influence of the Project-Based Learning (PjBL) model, when integrated with the STEM approach, on students’ collaborative abilities in the topic of atomic structure. The study is motivated by the persistent issue of low collaboration levels among chemistry learners, particularly when dealing with abstract subject matter. Employing a quantitative methodology with a quasi-experimental design—specifically the Non-Equivalent Control Group Design—the research was conducted with two tenth-grade classes at SMA Negeri 1 Suwawa, designating one as the experimental group and the other as the control group. Data were gathered through observation sheets that measured five aspects of collaboration: cooperation, responsibility, communication, adaptability, and compromise. The findings revealed a notable enhancement in collaborative skills within the experimental class following the application of the STEM-integrated PjBL model. The average final observation score for this group reached 76%, surpassing the control group’s 61%. The N-Gain score for the experimental group fell within the medium category (0.48), whereas the control group’s score was classified as low (0.17). Improvements were recorded across all collaboration indicators. Overall, the results suggest that the STEM-integrated PjBL model is effective in fostering collaboration skills and can be recommended as an alternative instructional approach for other chemistry topics to advance 21st-century skill development.